5-Aminosalicylates reduce the risk of colorectal neoplasia in patients with ulcerative colitis: an updated meta-analysis. - Li-Na Zhao; Jie-Yao Li; Tao Yu; Guang-Cheng Chen; Yu-Hong Yuan; Qi-Kui Chen (PLoS ONE, 2014)
Background Although the chemopreventive effect of 5-aminosalicylates on patients with ulcerative colitis has been extensively studied, the results remain controversial. This updated review included more recent studies and evaluated the effectiveness of 5-aminosalicylates use on colorectal neoplasia prevention in patients with ulcerative colitis. Methods Up to July 2013, we searched Medline, Embase, Web of Science, Cochrane CENTRAL, and SinoMed of China for all relevant observational studies (case-control and cohort) about the effect of 5-aminosalicylates on the risk of colorectal neoplasia among patients with ulcerative colitis. The Newcastle-Ottawa Scale was used to assess the quality of studies. Adjusted odds ratios (ORs) were extracted from each study. A random-effects model was used to generate pooled ORs and 95% confidence intervals (95%CI). Publication bias and heterogeneity were assessed. Results Seventeen studies containing 1,508 cases of colorectal neoplasia and a total of 20,193 subjects published from 1994 to 2012 were analyzed. 5-aminosalicylates use was associated with a reduced risk of colorectal neoplasia in patients with ulcerative colitis (OR 0.63; 95%CI 0.48-0.84). Pooled OR of a higher average daily dose of 5-aminosalicylates (sulfasalazine ≥ 2.0 g/d, mesalamine ≥ 1.2 g/d) was 0.51 [0.35-0.75]. Pooled OR of 5-aminosalicylates use in patients with extensive ulcerative colitis was 1.00 [0.53-1.89]. Conclusion Our pooled results indicated that 5-aminosalicylates use was associated with a reduced risk of colorectal neoplasia in patients with ulcerative colitis, especially in the cases with a higher average daily dose of 5-aminosalicylates use. However, the chemopreventive benefit of 5-aminosalicylates use in patients with extensive ulcerative colitis was limited.